PELAKSANAAN MANAJEMEN HUMAS DI SDQT NURUL ISLAM DALAM MENDUKUNG HUBUNGAN SEKOLAH DENGAN MASYARAKAT - Muhamad Arifin Ilham; Lilis Karyawati; Nur Aini Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation of public relations management at SDQT Nurul Islam and its role in establishing relationships with the community. The study uses a qualitative approach through interviews with educational staff. The results show that public relations management does not yet have a formal structure and is carried out collaboratively by operators, administrators, homeroom teachers, and teachers who manage social media. PR activities are more focused on internal communication with parents via WhatsApp, handling complaints, and weekly recitations. Its implementation still faces obstacles in the form of limited human resources and suboptimal use of digital media. This study concludes that the role of PR has been carried out, but organizational strengthening and a more systematic communication strategy are still needed.